Pencemaran Tanah Oleh Pestisida Di Perkebunan Sayur Kelurahan Eka Jaya Kecamatan Jambi Selatan Kota Jambi (Studi Keberadaan Jamur Makroza dan Cacing Tanah) - Supriatna Supriatna; Sondang Siahaan; Indah Restiaty (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Healthy vegetables can only be from healthy and pollution-free farmland, including pesticide pollution. When a harmful or toxic substance has contaminated the surface of the soil, it can evaporate, be swept away by rainwater and or enter the soil. Pollution that enters the soil is then immersed as toxic chemicals in the soil. Toxic substances in the soil can have a direct impact on humans when touched or can contaminate groundwater thus lowering the function of the soil as a place of growing and developing plants. The purpose of this study is to find out the picture of soil pollution by pesticides and the presence of earthworms and mycoriza fungi in the soil. The use of pesticides that are not in accordance with the rules and formulations cause pollution to vegetables and the environment such as soil and water. By taking soil samples and checking the content of pesticides can be known whether the pesticides used have polluted the soil. The presence of worms and mycoriza will be less and less even none at all on the soil that has been polluted. The results showed that from six soil sampling locations found two locations of carbamate pesticide pollution (33.3%), no mycoriza mushrooms were found at one location (15.6%) and earthworms are found throughout the site (100%). Pollution occurs because vegetable farmers and palawija use pesticides exceeding the recommended dose and occur pengulang in the adjacent time span. Mycoriza mushrooms are found in the form of spores, fungal spores have a stronger survival ability compared to the whole stem of the mycoriza fungus. Earthworms derived from manure used as fertilizer, in addition to its ability to avoid toxic soil mucus presence in his body can protect tabnah cacaing from pesticide exposure.